Servant Leadership: A Systematic Literature Review of Definitions, Measurement, and Its Effects on Employee Performance and Well-Being (2010–2025): Kepemimpinan Pelayan: Tinjauan Literatur Sistematis tentang Definisi, Pengukuran, dan Pengaruhnya terhadap Kinerja dan Kesejahteraan Karyawan (2010–2025) - Faizal Rachman; Bambang Karsono; Tri Widyastuti (Jurnal Bisnis dan Ekonomi, 2026)
Abstract : Servant leadership emphasizes prioritizing followers’ needs, moral values, and the development of individuals within organizations.   Objective: This systematic literature review explores theoretical advancements, measurement instruments, and empirical evidence of servant leadership from 2010 to 2025.   Methods: The analysis covers antecedents, mediating mechanisms, and organizational outcomes, including performance, well-being, and innovation.   Results: The review finds consistent evidence of positive relationships between servant leadership and job satisfaction, trust, and organizational citizenship behavior, mediated by psychological safety and meaningfulness. Practical and theoretical implications are discussed.